Communications mode(l)s and disasters: from word of mouth to ICTs - Maria Paradiso (Netcom)
Information and communication technologies present significant advances in spatially-related information and communication systems. They may greatly enhance disaster prevention and crisis management. However, the ways by which ICTs culturally affect people-environment relations (hazard perception, citizen preparedness, relief, recovery, and resilience) have not been sufficiently investigated. This paper attempts to compare people’s behaviour when coping with hazards and disasters along three ages: oral word, mass media mediation, and ICTs mediation. The paper then presents an overarching model of coping with disasters and guidelines for ICT uses in a full disaster cycle.